Genetic analysis of seed coat colour in adzuki bean (Vigna angularis L.). Issue 1 (22nd February 2021) - Chu, Liwei; Zhao, Pu; Huang, Xueqi; Zhao, Bo; Li, Yisong; Yang, Kai; Wan, Ping
Abstract: Seed coat colour is an important quality trait, domestication trait and morphological marker, and is closely associated with flavonoid and anthocyanin metabolism pathways. The seed coat colour of adzuki bean, an important legume crop, influences the processing quality of its paste, the commodity and its nutritional quality. In this study, the genetic relationships of seed coat colour were analysed using 12 hybridized combinations of F2 individuals and four F3 families derived from hybridized combinations between the accessions of eight seed coat colours. The loci of the colour traits were analysed based on phenotypes and using the chi-square test. Ivory colour is recessive to red and is controlled by a single R locus. Black, black mottle on grey, black mottle on red, light brown, golden and brown are all dominant to red. The phenotypes of black mottle on red, light brown, golden and brown are all controlled by a single genetic locus. Black mottle on grey is controlled by two loci. Black is controlled with two loci, and the black locus shows dominant epistasis to another locus. A genetic model of these seed coat colours was predicted. Our results will be important for gene mapping and cloning of seed coat colour characters and for providing further insight into the regulatory network of seed coat colour.